Suppression of lncRNA RMRP ameliorates oxygen-glucose deprivation/re-oxygenation-induced neural cells injury by inhibiting autophagy and PI3K/Akt/mTOR-mediated apoptosis. Issue 6 (25th June 2019) - Zhou, Zheyi; Xu, Hong; Liu, Baozhu; Dun, Linglu; Lu, Changjun; Cai, Yefeng; Wang, Honghao
Abstract : The aberrant expression of lncRNAs has been inferred to be closely related with the progression of neural ischemia/reperfusion (I/R) injury. RMRP is an lncRNA associated with I/R injury. In order to determine the role of RMRP in I/R injury, the effects of RMRP knockdown on oxygen-glucose deprivation/re-oxygenation (OGD/R)-induced injury in SH-SY5Y cells were evaluated. The effect of OGD/R administration on the expression of RMRP and apoptosis in SH-SY5Y cells, and the effect of RMRP suppression by siRNA on the impairments of cells proliferation and mobility potential due to OGD/R administration were assessed in the current study. At the molecular level, the current study detected the expressions of indicators involved in autophagy and PI3K/Akt/mTOR-mediated apoptosis pathways. The OGD/R administration induced the expression of RMRP and apoptosis in SH-SY5Y cells. After RMRP knockdown, the proliferation potential of SH-SY5Y cells was restored, and apoptosis and cell cycle arrest were inhibited. Moreover, RMRP inhibition also increased the invasion and migration of SH-SY5Y cells which were treated with OGD/R. The effects of RMRP suppression on the phenotypes of SH-SY5Y were associated with the inhibition of LC3II, p-PI3K, p-Akt, and p-mTOR as well as the induction of P62 and Bcl-2. Inhibition of RMRP contributed to the improvement of OGD/R-induced neuronal injury, which might be mediated through the inhibition of autophagy and apoptosis pathways.